Empirical Investigation of Customers’ Perception and Adoption Towards Islamic Banking Services in Morocco - Echchabi, Abdelghani; Abd. Aziz, Hassanuddeen (2012)
The main purpose of the study is to examine the willingness of the Moroccan customers to adopt Islamic banking services and the factors that may influence their decision. A total of 200 questionnaires were randomly distributed to Moroccan banking customers, out of which 146 were properly filled and returned. Multiple regression and one sample t-test were subsequently applied. The results showed that uncertainty, relative advantage, compatibility, awareness as well as subjective norm, have a significant impact on the attitude towards Islamic banking services in Morocco. Likewise, normative belief was also found to have a significant influence on subjective norm, with particular reference to the parents, siblings, peers and colleagues, as the main referent groups. In addition, facilitating conditions was found to have a significant influence on perceived behavioural control and finally attitude, subjective norm and perceived behavioural control were found to have a significant impact on the intention to adopt Islamic banking services in Morocco. It is worth noting that complexity does not have any influence on attitude and self efficacy does not have any influence on perceived behavioural control as well. On the other hand, the results have also shown that the Moroccan customers are willing to shift to Islamic banking services, with a slight preference of long run adoption i.e. three years and above. This study is one of the earliest to be conducted on customers’ perception and willingness to adopt Islamic banking services in Morocco. The study also extends the decomposed theory of planned behaviour to a different setting and also to a different area of study.